Characterization of patients with hepatocellular carcinoma on the way for early detection: one center experience - Salah Elgamal; Ahmed A Ghafar; Elsayed Ghoneem; Moustafa Elshaer; Hani Alrefai; Wafaa Elemshaty (SpringerOpen, 2018)
Background Hepatocellular carcinoma (HCC) is the commonest primary liver neoplasm that usually develop in the background of cirrhosis. Hepatitis C virus is endemic in Egypt and is the major cause of cirrhosis. Studying the characteristics of patients with HCC may help in clarifying the schedule for screening of high-risk patients for an early detection of HCC. Patients and methods The 492 patients attending the hepatology and HCC clinics in Specialized Medical Hospital, Mansoura University for follow up of liver cirrhois and HCC were subjected to full history, physical examination, laboratory profile, and imaging studies needed for the diagnosis. Data were collected and analyzed. According to the radiological results, patients were divided into three groups (fibrosis, cirrhosis, and HCC) and compared. Results The study included 336 males and 156 females. Patients with HCC were mainly males with a mean age of 58 years. A statistically significant difference between HCC group and the other groups with respect to hemoglobin level, white blood cells count, platelet count, aspartate aminotransferase, alanine aminotransferase, albumen level, serum bilirubin, international normalized ratio, and α-fetoprotein (AFP) was found. The sensitivity and specificity of AFP in differentiating HCC cases are 81.1 and 71.9%, respectively. Logistic regression for prediction of HCC showed that males with age greater than 58 years, hypoalbuminaemia, and AFP greater than 11.2 ng/dl have a 76.3% positive predicted value. Conclusion Cirrhotic patients with age greater than 58 years, males, hypoalbuminaemia, and AFP greater than 11.2 ng/dl are at a higher risk to develop HCC more than other patients and should be monitored at close quarters with better contrast-enhanced technique either contrast-enhanced ultrasound or computed tomography scan.